Growth of cowpea submitted to mineral fertilization and different doses of biofertilizer - Sousa, Mateus Alves de; Avelino, Victor Sousa; Reis, Iolanda Maria Soares (Scientia Agraria Paranaensis, 2021)
In the Northern region, the cultivation of cowpea is mainly carried out by small producers, who have little financial and technological resources to optimize and increase production. Therefore, the objective of this work was to evaluate the growth of cowpea subjected to mineral fertilization and doses of biofertilizer produced in domestic compost. The experiment was carried out in a protected environment, covered with a 50% shade screen, at the Federal University of Western Pará (UFOPA), Santarém PA, in 2017. Seeds were arranged in 5 L pots, containing 3.5 Kg of Yellow Latosol. For sowing, 3 seeds per pot were used and thinning occurred 7 days after seedling emergence, leaving only the most vigorous. The experimental design used was randomized blocks, with subdivided plots, where the plots were the doses of biofertilizer (50, 100, 150 and 200 mL plant-1 + mineral fertilizer) and the subplots, the time periods: T1 (0 to 20 days), T2 (24 to 33 days), T3 (37 to 47 days) and T4 (51 to 61 days), containing five repetitions. Plant height, stem diameter, absolute stem growth rate and absolute growth rate in stem thickness were evaluated. The greatest growth of cowpea was obtained in treatments with mineral fertilization. The dose of 200 mL plant-1 of the biofertilizer showed results close to mineral fertilization, in different vegetative stages. Cowpea plants, starting at 45 DAE, tend to stabilize their growth in diameter.